P91 Can healthcare professionals in a respiratory unit correctly set an oxygen flow rate on a standard oxylitre medical regulator?. (16th November 2010) - Billington, S J; Mordaunt, C; Angus, R M; Spencer, L G
Abstract : Background: It is known that prescribing practice in UK hospitals for oxygen is often suboptimal. In our Trust we are already working towards improving oxygen prescription practice. However, if we improve prescribing but do not ensure administration is also robust then patient safety will not be achieved. There is potential for serious harm and even death if oxygen management is incorrect (National Patient Safety Agency 2009/RRR006). We investigated how accurate our oxygen administration practice is. Method: Between January and March 2010 we randomly approached 100 healthcare professionals working on our respiratory wards. They were asked (1) to demonstrate where they would position the ball on a standard oxylitre medical regulator to set a flow rate of 2 l of oxygen per minute, (2) whether they had received training in the use of oxygen flow metres and (3) if they had completed the Trusts self-assessment competency form for the use of oxygen flow metres. Results: Of the 100 staff approached 49 were nurses (various grades), 25 doctors (various grades), six physiotherapists, 19 nursing and one medical student. 65 staff set the flow rate correctly, with 33 setting it too high, that is, above the appropriate line and two too low, that is, below the line. 24 (24%) staff had received either formal (medical or nursing school) or informal (from a colleague) training in the use of flow metres. Only seven of the staff had completed the Trusts self-assessment competency form; they all set the flow correctly. Discussion: The NPSA report 2009 identified a national problem regarding the inappropriate administration and management of oxygen. Our study indicates deficiencies in our practice in this specialist unit. There is a lack of clinical training and a low uptake of the self-assessment competency form. With these observations we are moving to make training and competency assessment mandatory for all clinical staff across the Trust. Also with the confusion we observed in correctly setting our hospitals traditional regulators we are considering switching to calibrated flow metres with a 'dial' to select flow which would reduce room for error and make oxygen administration safer.